Pengaruh Pelatihan, Kompetensi Dan Lingkungan Kerja Terhadap Kinerja Karyawan PDAM Tirtanadi Sei Agul - Sri Suganti; Nina Agustina; Demak Claudia Yosephine Simanjuntak (CERED Indonesia Institute, 2021)
This study aims to analyze the impact of training, competence and work environment on the performance of PDAM Tirtanadi Sei Agul employees. The population is 120 people and the sample in this study is 92 people. Testing using multiple linear analysis techniques partial hypothesis test results obtained that the training has a value of tcount> ttable that is 2.682> 1.66235 with a significant level of 0.009 <0.05, competence has a value of tcount> ttable that is 3.391> 1.66235 with a significant level of 0.001 < 0.05 and the work environment has a value of tcount> ttable that is 6.281 > 1.66235 with a significant level of 0.000 <0.05 so that training, competence and work environment have a significant and significant effect on the performance of PDAM Tirtanadi Sei Agul employees. Simultaneous test results obtained that the value of Fcount > Ftable is 44,662 > 2.71 with a significant level of 0.000 < 0.05 so it can be concluded that training, competence and work environment have a significant and joint effect on the performance of PDAM Tirtaadi Sei Agul employees.